Hookah profiles, their perception towards effects of hookah use on health and healthy life style behaviors of healthcare professionals - Topcu, Merve; Zorlu, Semra (Journal of Dependence, 2021)
Objective: The aim of this study is to determine hookah smoking profiles of health personnels, perceptions of health effects of hookah and healthy lifestyle behaviors.Method: The study was conducted on 526 health personnels including physicians, nurses and midwives working in three different hospitals. Data of study were collected through Personal Information Form, Perception Scale Effects of Hookah use on Health (PSEHH), Healthy Lifestyle Behaviors Scale (HLBS).Results: The use of hookah was found to be 46.2% in male health personnels and 53.8% in female health personnels. It has been revealed that there is a positive significant relationship between mean scores of PSEHH and HLBS, and with the increase in the perception effects of hookah on health, healthy lifestyle behaviors increase. It was determined that being a male health worker increased probability of hookah smoking by 2.247 times, being still smoking increased 1.507 times.Conclusion: Health personnels with higher perceptions health effects of hookah show healthy lifestyle behaviors more. In order to increase the awareness of health personnels regarding hookah use, it is recommended that tobacco addiction, its roles and responsibilities in tobacco control should be adequately covered in vocational education curricula.
Keywords: Health personnel; hookah smoking; perception; healthy lifestyle; nursing